The effect of plant invasion on soil microbial carbon‐use efficiency in semi‐arid grasslands of the Rocky Mountain West. (6th December 2021) - Nasto, Megan K.; McLeod, Morgan Luce; Bullington, Lorinda; Lekberg, Ylva; Stark, John M.
Abstract: Grassland ecosystems invaded by exotic plant species often exhibit substantially higher above‐ground productivity and soil nitrogen (N) than the native communities they replace. These shifts are likely associated with altered microbial carbon (C) and N cycling, but we know surprisingly little about how these processes change with plant invasion. Targeting four invasive plant species common in the Rocky Mountain West, we collected soils from invaded and adjacent uninvaded grassland field plots, as well as from an experimental garden. We used a laboratory incubation of soils with 13 C‐ and 15 N‐labelled substrates to examine how microbial C respiration, C assimilation and N cycling differed among plant communities. To assess how these rates corresponded with plant productivity and microbial communities, we measured above‐ground plant biomass and characterized bacterial and fungal communities using Illumina sequencing. In the paired observational plots, soil microbial communities associated with invaders generally had higher respiration rates and lower growth rates than those associated with the native plant communities, leading to a lower microbial carbon‐use efficiency (CUE). Overall, soil substrate with a lower C:N was related to decreased CUE, and lower CUE was related to increased gross and net N mineralization. In turn, faster gross N mineralization was related to greater above‐ground biomass. These patterns coincided with significant differences in fungal communities, whereas bacterial communities varied by site. Invasive plants also altered microbial communities in the experimental plots, but this was not associated with shifts in microbial CUE, which was low overall. Synthesis . Our results provide evidence that invasive plants alter bacterial and fungal communities. These shifts were not associated with changes in microbial CUE and, thus, the often‐assumed link between compositional and functional shifts was not apparent in this study. However, lower CUE was associated with elevated rates of N cycling and productivity, which, in low‐productivity systems, could help explain the increased growth and success of exotic plant invaders. Abstract : The invasive plants we studied in a Rocky Mountain semi‐arid grassland harboured soil microbial communities with a lower carbon‐use efficiency than their neighbouring native plant assemblages. The low CUE of invasive plants was associated with elevated rates of N cycling and productivity, which, in low‐productivity systems, could help to explain the increased growth and success of exotic plant invaders.